EFFECT OF WASTE GLASS POWDER ON COW DUNG ASH CONCRETE (FUDMA JOURNAL OF SCIENCES, 2023)
The focus of this study is to determine the influence of the waste glass powder (WGP) on Cow Dung Ash (CDA) concrete. The CDA and WGP were used as partial replacement of cement where CDA was kept constant at 10 % while the WGP was used at 2, 4, 6, 8 and 10 %. A seven batches of concrete were produced for the curing age of 7, 14, and 28 days. After the preliminary tests the following aspect were focused on: consistency, setting time, workability and strength. The result showed that consistency increased with 10 % replacement of cement with CDA and that 6 % is the optimum content of WGP for consistency. The setting times of binder paste increased with 10 % replacement of cement with CDA and then continuously increasing with introduction of WGP at 2, 4 , 6 % replacement. However, the maximum initial and final setting times were attained at 6 % of WGP. The workability of concrete had been found to be decreased with CDA and gradually increased with the introduction of WGP as cement replacement. The compressive strength increased with 10 % replacement of cement with CDA, and then increased continuously with 2%, 4%, replacement of cement with WGP before it declined and increased to a maximum at 8 %. Thus the optimum content of WGP is 8 % and the compressive strength increased. Production of concrete from waste materials saves energy, enhance strength and conserves resources which lead to a safe sustainable environment
Keywords: Glass Powder, Cow Dung Ash, Concrete, Consistency, Compressive strength